The Relationship Self Compassion and Resillience with Parenting Stress in Parents of Dyslexia Children: Self Compassion, Resilience, Parenting Stress, Dyslexia - Koesnita, Dian; Suroso; Pratitis, Niken Titi (Kirana Publisher (KNPub), 2025)
This research aims to empirically test the relationship between self-compassion and resilience and parenting stress in parents of dyslexic children. Self-compassion or self-love which consists of aspects of self-kindness, common humanity and mindfulness as well as resilience which is a person's ability to solve problems in adapting themselves to difficulties that occur becomes capital for someone to overcome negative emotions so that they can make positive efforts in dealing with stressors in parenting. for children who have dyslexia. This research uses a correlational quantitative approach. Data was obtained from 135 parents who have dyslexic children using the parenting stress scale, self-compassion scale and resilience scale. Research analysis uses parametric analysis techniques, Multiple Regression Analysis. The research results show that self-compassion and resilience have a very significant negative correlation with parenting stress in parents of dyslexic children.